U.S. security-related agreements in force since 1955 : introducing a new database - Kavanagh, Jennifer, 1981- (Technical report (Rand Corporation), 2014)
Treaties and agreements are powerful foreign policy tools that the United States uses to build and solidify relationships with partners and to influence the behavior of other states. As a result, the overall U.S. portfolio of treaties and agreements can offer insight into the distribution and depth of U.S. commitments internationally, including its military commitments and 'presence' in a given country or region. However, despite their importance, there is currently no comprehensive record of current or historical security-related treaties signed by the United States that can be used for empirical analysis. To address the shortcomings in existing datasets and indexes to contribute to the study of U.S. security treaties and agreements, we have developed a new, more comprehensive treaty database that will enhance the ability of researchers to study the full portfolio of U.S. security agreements. This report discusses our approach to data collection and coding and also presents a summary of the database's content. Its appendixes define each individual variable used in the analysis. The database was developed as part of a larger project focused on estimating the economic value of U.S. military presence overseas. In the context of this larger project, the treaty database provided an alternative way to measure 'military presence.' In addition to using numbers of troops as a measure of presence, we also used numbers of security-related agreements, drawing on the information in the treaty database described in this report. This measure provided us with additional insight into the value and role of U.S. engagement and operations in overseas areas.